2018
DOI: 10.3390/agriculture8040051
|View full text |Cite
|
Sign up to set email alerts
|

22 Years of Governance Structures and Performance: What Has Been Achieved in Agrifood Chains and Beyond? A Review

Abstract: Although the existing literature has shown that the choice of governance structure plays a key role in inter-organizational performance, the nature of construct measurability still remains equivocal. The diversity of terminologies used means that the full potential of most studies may be lost in the confusion of indistinctive and misapplied terms. To better understand the relationship between governance structures and performance, a descriptive systematic review was conducted on the extant literature; essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 188 publications
(243 reference statements)
0
10
0
1
Order By: Relevance
“…Papers in which negative or partially negative results are published are indicated in bold text (negative results are understood as meaning no multiplier effect was found, or that the multiplier effect found in the local food context was less than that of conventional production). Due to the low number and heterogeneity of the applied methods, qualitative assessments were included, in a similar manner to the syntheses prepared by [45,48,51], although there were fewer papers involved in the analysis in our case.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Papers in which negative or partially negative results are published are indicated in bold text (negative results are understood as meaning no multiplier effect was found, or that the multiplier effect found in the local food context was less than that of conventional production). Due to the low number and heterogeneity of the applied methods, qualitative assessments were included, in a similar manner to the syntheses prepared by [45,48,51], although there were fewer papers involved in the analysis in our case.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, a process that follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [40,43] is introduced. PRISMA, although originally developed in a healthcare context, is a popular and rigorous guideline that is also used in the field of agricultural economics [2,[44][45][46], among other areas, when analyzing and reporting on search-related results. To establish greater scientific rigor, the protocol for the present systematic review process was discussed at the 174th Seminar of the European Association of Agricultural Economists in Matera, Italy in October 2019.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…'The performance measurement has proven to be a difficult task, especially in agrifood chains.' [90] (p. 53). In the field of internationalization and firm performance, prior research underplays the roles of management [43,44].…”
Section: The Use Of Mcss In Internationalizing Companiesmentioning
confidence: 99%
“…Growers and producers of fresh produce are required to comply with codes and private standards set by supermarkets (Tallontire et al 2011), which are a dominant form of governance in agri-food chains (Bair 2005). A review of agri-food governance identified the type of governance was influenced by coordination strategies, with a combination of relational and contractual governance needed to optimise performance (Kataike & Gellynck 2018). Relational governance curtails opportunism, complements contracts (Zhou & Xu 2012), decreases uncertainty and transaction costs (Dolci et al 2017).…”
Section: Supply Chain Governancementioning
confidence: 99%